2009
DOI: 10.2147/ibpc.s6232
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in combination therapy for the treatment of hypertension: combined calcium channel blockers and RAAS inhibitors

Abstract: Recent guidelines for the management of hypertension recommend target blood pressures <140/90 mmHg in hypertensive patients, or <130/80 mmHg in subjects with diabetes, chronic kidney disease, or coronary artery disease. Despite the availability and efficacy of antihypertensive drugs, most hypertensive patients do not reach the recommended treatment targets with monotherapy, making combination therapy necessary to achieve the therapeutic goal. Combination therapy with 2 or more agents is the most effective meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
(51 reference statements)
1
20
0
3
Order By: Relevance
“…Furthermore, guidelines suggest the initial use of combination therapy if BP is > 160/100 mmHg, or to combine drugs with different mechanism of action when the goal of BP < 140/90 mmHg is not achieved with monotherapy [Rubio-Guerra et al 2009]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, guidelines suggest the initial use of combination therapy if BP is > 160/100 mmHg, or to combine drugs with different mechanism of action when the goal of BP < 140/90 mmHg is not achieved with monotherapy [Rubio-Guerra et al 2009]. …”
Section: Discussionmentioning
confidence: 99%
“…Clinicians have many drug choices; the combinations of inhibitors of the renin-angiotensin-aldosterone system (RAAS) plus calcium antagonists, or a thiazide are efficacious and well tolerated, and both represent a real addition to the available antihypertensive treatment options [Rubio-Guerra et al 2009]. However, few data are available on the effect of antihypertensive combination therapy on serum uric acid levels.…”
Section: Introductionmentioning
confidence: 99%
“…By combining two drugs with different mechanisms of action, an antihypertensive effect of two to five times greater than that obtained by monotherapy is possible [ 7 , 8 ]. Increasing the dose of monotherapy reduces coronary events by 29% and cerebrovascular events by 40%, while combining two antihypertensive agents with a different mechanism of action reduces coronary events by 40% and cerebrovascular events by 54% [ 9 ]. Thus, the use of combination therapy provides greater protection to a target organ than increasing the dose of monotherapy.…”
Section: Rationale For Combination Therapymentioning
confidence: 99%
“…Although some studies have reported the effect of L/T-, L/N-, or L/N/T-type CCBs on estimated GFR (eGFR), their results vary according to concomitant drugs, treatment duration, and medical history of the patients [ 6 , 7 , 10 ]. In addition, some CCBs are known to cause an increase in GFR, hyperfiltration, and edema in the acute phase of initiation of treatment in patients with CKD [ 11 13 ]. Agodoa et al reported that eGFR increased during the first 3 months of treatment with amlodipine, an L-type CCB, but decreased after 36 months in patients without proteinuria [ 14 ].…”
Section: Introductionmentioning
confidence: 99%